2005
DOI: 10.4049/jimmunol.175.12.7939
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term MHC Class II Presentation of the EBV Lytic Protein BHRF1 by EBV Latently Infected B Cells following Capture of BHRF1 Antigen

Abstract: Although T lymphocytes are considered essential for the control of EBV infection, it remains uncertain how this control occurs. We previously reported unexpected killing of EBV-transformed B-lymphoblastoid cells (LCLs) that did not express BHRF1 by CD4+ T cells specific for BHRF1, an EBV lytic cycle protein. Using LCLs transformed with an EBV mutant, in which the BHRF1 gene was deleted, we showed that killing of latently infected cells through the recognition of a protein produced during the lytic cycle is due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…By contrast, the recognition of semipermissive LCL cells by virus-structural Ag-specific CD4 ϩ T cells was found to be dependent upon the intercellular transfer of virions within the culture (54). Furthermore, a similar example of LCL recognition by CD4 ϩ T cell clones against the nonstructural lytic cycle protein BHRF1 has been ascribed to slow charging of the HLA class II pathway by Ag released from lytically infected cells (55).…”
Section: Discussionmentioning
confidence: 91%
“…By contrast, the recognition of semipermissive LCL cells by virus-structural Ag-specific CD4 ϩ T cells was found to be dependent upon the intercellular transfer of virions within the culture (54). Furthermore, a similar example of LCL recognition by CD4 ϩ T cell clones against the nonstructural lytic cycle protein BHRF1 has been ascribed to slow charging of the HLA class II pathway by Ag released from lytically infected cells (55).…”
Section: Discussionmentioning
confidence: 91%
“…5A). To address whether the presentation of BMRF1 involved intercellular protein transfer as recently described for latent cycle proteins [36] and the lytic cycle protein BHRF1 [37], autologous mini-LCL were co-cultured with MHC-mismatched LCL for 24 hours. T cell recognition of the cell mixture, but neither component alone, indicated that antigen released from cells undergoing lysis is transferred to neighboring cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In cultures of the transduced cells, exogenous loading of the HLA class II molecules by peptides taken up from neighboring cells was not very likely as demonstrated in the 5-day coculture experiments, although it cannot be excluded that longer periods of coculture would have been necessary to observe such events. It was reported recently that, in cultures of B-LCL, transfer of BHRF1 Ag derived from the few cells entering lytic cycle to latently infected cells could take as long as 21 days (70). Thus, despite these limitations, our experiments suggest that the same functional HAdV epitope can be presented via both an exogenous as well as an endogenous pathway.…”
Section: Discussionmentioning
confidence: 72%